Comparison of the accuracy of digitally fabricated polyurethane model and conventional gypsum model - Kim, So-Yeun (The Korean Academy of Prosthodontics, 2014)
PURPOSE: The accuracy of a gypsum model (GM), which was taken using a conventional silicone impression technique, was compared with that of a polyurethane model (PM), which was taken using an iTero™ digital impression system. MATERIALS AND METHODS: The maxillary first molar artificial tooth was selected as the reference tooth. The GMs were fabricated through a silicone impression of a reference tooth, and PMs were fabricated by a digital impression (n=9, in each group). The reference tooth and experimental models were scanned using a 3 shape convince™ scan system. Each GM and PM image was superimposed on the registered reference model (RM) and 2D images were obtained. The discrepancies of the points registered on the superimposed images were measured and defined as GM-RM group and PM-RM group. Statistical analysis was performed using a Student's T-test (α=0.05). RESULTS: A comparison of the absolute value of the discrepancy revealed a significant difference between the two groups only at the occlusal surface. The GM group showed a smaller mean discrepancy than the PM group. Significant differences in the GM-RM group and PM-RM group were observed in the margins (point a and f), mesial mid-axial wall (point b) and occlusal surfaces (point c and d). CONCLUSION: Under the conditions examined, the digitally fabricated polyurethane model showed a tendency for a reduced size in the margin than the reference tooth. The conventional gypsum model showed a smaller discrepancy on the occlusal surface than the polyurethane model.